Genome and GWAS analyses for soybean cyst nematode resistance in USDA world-wide common bean (Phaseolus vulgaris) germplasm - Shi, Ainong; Xiong, Haizheng; Michaels, Thomas E.; Chen, Senyu (Frontiers in Plant Science, 2025)
Soybean cyst nematode (SCN), Heterodera glycines, has become a significant threat in common bean (Phaseolus vulgaris) production, particularly in regions like the upper Midwest USA. Host genetic resistance offers an effective and environmentally friendly approach to managing SCN. This study aimed to conduct a genome-wide association study (GWAS) and genomic prediction for resistance to SCN HG Types 7 (race 6), 2.5.7 (race 5), and 1.3.6.7 (race 14) using 0.7 million whole-genome resequencing-generated SNPs in 354 USDA worldwide common bean germplasm accessions. Among these, 26 lines exhibited resistance to all three HG types, with a female index (FI) of less than 10. Four QTL regions on chromosomes (Chr) 2, 3, 6, and 10 were associated with resistance to HG Type 7; four regions on Chrs 2, 6, 9, and 11 were associated with resistance to HG Type 2.5.7; and three regions on Chrs 2, 6, and 10 were associated with resistance to HG Type 1.3.6.7. Cross-prediction revealed high prediction ability (PA) of 75% (r-value) for resistance to each of the three HG types. However, low PA was observed for SCN resistance through across-population prediction between the two domestications, Mesoamerican and Andean common bean accessions. Yet, using a population of mixed Mesoamerican and Andean accessions as a training set showed a high PA to predict either sub-population. This study provides SNP markers for marker-assisted selection and high PA for genomic selection in common bean molecular breeding, enabling the selection of lines and plants with high SCN resistance. Moreover, the study observed high PA for resistance among the three HG types. Interestingly, the most highly associated SNP markers and QTL for SCN resistance varied between the two domestications, and SCN resistance is more associated with the Mesoamerican domestication than the Andean domestication. This result suggests that resistance to SCN in common bean may be related to domestication rather than co-evolution with SCN.